Communicative Elements of Action Research - Thomas G Ryan (Networks: An Online Journal for Teacher Research, 2013)
This review considers human communications as utilized within a research design; in this case collaborative action research (CAR), a derivative of action research (AR), to achieve outcomes that change, and move participants forward. The association between AR and CAR is a deliberate attempt by the author to draw attention to communicative actions within each mode. Communication herein emerges via two channels, the nonverbal and verbal which combine to produce meaning in AR and CAR as researchers investigate. CAR was defined via numerous understandings of AR which were presented as a means to develop professionally. AR as reflective practice is presented, as is reflexivity within human communication that infuses research action and teacher development.